Dampak Ekonomi Dari Covid-19 Dan Pemanfaatan Insentif Pajak Terhadap Keberlangsungan Usaha UMKM Kota Cimahi. - Larasati, Anissa Yuniar; Purwanto, Purwanto (JPAK : Jurnal Pendidikan Akuntansi dan Keuangan, 2022)
This research was conducted to find out how much of the economic impact of covid-19 and the intensive utilization of taxes on the sustainability of MSMEs in the city of Cimahi. The research method used is to use quantative research methods. This study used probability sampling through a simple random sampling approach and was calculated with the slovin formula that produced 100 samples. The data collection in this study used observations, literature studies and questionnaires. The study allocates multiple regression tests, t tests, f tests and coefficients of determination. Based on the results of research conducted partially the economic impact of covid-19 has an insignificant negative effect on the sustainability of MSME business in the city of Cimahi, while the tax intensive affects the sustainability of MSME business in the city of Cimahi and simultaneously the economic impact of covid-19 and the intensive utilization of taxes has a positive and significant effect on the sustainability of MSME business in the city of Cimahi.